Potential for improved transport in core–shell CuInS2 nanoparticle solar cells from an Ag surface termination. Issue 24 (31st May 2018) - Hu, Yicong; Patterson, Rob; Lee-Chin, Robert; Zheng, Jianghui; Song, Ning; Hu, Long; Conibeer, Gavin; Huang, Shujuan
Abstract : Improvements in charge carrier transport and equivalent photoluminescence were obtained for CuInS2 nanoparticles with Ag-surface termination in photovoltaic devices. Abstract : A major factor limiting the performance of nanostructured CuInS2 photovoltaic devices is the current density, pointing to poor charge carrier transport in CuInS2 nanoparticle films. In a typical CuInS2 core/shell structure synthesis, ZnS is typically chosen as a shell material for CuInS2 core passivation, which leads to a significant enhancement of the photoluminescence quantum yield from the CuInS2 nanoparticles. While typically a marker for excellent photovoltaic performance, in this case the increased photoluminescence likely signals increased charge carrier confinement and reduced transport through any thin films fabricated from the nanoparticles. Here we show that replacing the typical divalent Zn cation surface termination with a monovalent Ag cation leads to small improvements in charge carrier transport through nanostructured films. This surface termination intentionally introduces lower energy electronic states directly at the surface of the CuInS2 nanoparticles, reducing charge carrier confinement and thus increasing charge carrier mobility between nanoparticles. The study assessed appropriate Ag molar ratios to be used in synthesis, with an 8% Ag : Cu ratio found to be optimal. The passivation offered by Ag surface termination appears comparable to that from Zn with strong photoluminescence observed in both cases. Slight improvements in the performance of all-solid-state nanoparticle CuInS2 photovoltaic devices are obtained, with current densities in the Ag surface terminated case being increased by just under 10%. These findings outline a potential strategy for the synthesis of type II core–shell CuInS2 quantum dot thin film devices with improved charge transport.